Coupled influence of wettability alteration and geometry on two-phase flow in porous media. (November 2021) - Nemer, Mohamed N.; Rao, Parthib R.; Schaefer, Laura
Highlights: The interplay between wettability alteration and domain geometry in impacting pore-scale two-phase flow in porous media is investigated. A wettability alteration algorithm is developed and utilized to track spatial and temporal variation in the wettability state. The effect of wettability alteration on the oil phase fractional flow enhancement is more pronounced at comparable saturations of the two phases. The extent of oil ganglia remobilization and coalescence events due to wettability alteration are observed to be correlated with domain heterogeneity, capillary number, and phase saturation. The pore-scale displacement mechanisms are controlled by the local wettability state and pore topology, but the overall flow pathways are dictated by the interactions between the displacement mechanisms. The developed algorithm provides an efficient framework to track wettability alteration, update the wettability state, and detect trapped ganglia. Abstract: The objective of this paper is to investigate the interplay between wettability alteration and domain geometry in influencing the pore-scale displacement and trapping mechanisms of two-phase flow in porous media. A new wettability alteration algorithm is introduced to quantify and track the spatial and temporal variability of the wettability state of every pore. Simulations in an initially oil-wet domain are conducted using the lattice Boltzmann model while utilizing the wettability alteration algorithm to capture the new wettability states. The simulations are then resumed under the new generated wettability states to investigate the coupled impacts of wettability alteration and domain topology on the resulting pore-scale displacement behavior. We observe varying degrees of improvements in the oil phase fractional flow as the wettability state is varied towards water-wet conditions influenced by the domain geometry, capillary number, and phase saturation. Significant heterogeneity, increased surface roughness, and the prevalence of narrower pore spaces in the rock sample in comparison to the spherepack increase the percentage of trapped oil ganglia. As a result, wettability alteration results in varying degrees of oil remobilization events, followed by coalescence with the main flow path, especially at higher capillary numbers. Moreover, oil phase fractional flow at higher oil saturation becomes influenced primarily by the increased phase connectivity, and improvements due to wettability alteration become less significant. Similar displacement mechanisms are observed in both domains, controlled primarily by the wettability distribution and the local pore geometry. However, the resulting flow pathways, which dictate the overall flow behavior, are controlled by the frequency of various displacement mechanisms and are a function of the domain geometry. The observations in this study highlight the complex interactions between wettability heterogeneity and pore geometry in influencing pore-scale two-phase flow. The wettability alteration algorithm introduced can be used to optimize pore-scale displacement processes by providing a framework to track the locations and the relative degree of wettability alteration, enable automatic wettability alteration, and detect trapped ganglia without the need for post-processing.